Super-oscillatory optical needle - Savo, Salvatore (2013)
Super-oscillatory optical lenses have recently been shown to achieve subwavelength focusing and have been used for super-resolution imaging. However, the subwavelength hotspots created by these lenses are always accompanied by sidebands containing a significant fraction of the optical energy and are highly localised in the axial direction. Here, we report a class of super-oscillatory lenses that form extended subwavelength optical needles on a 15λ field of view.